Mitochondrial Complex I Function Is Essential for Neural Stem/Progenitor Cells Proliferation and Differentiation - Cabello-Rivera, Daniel; Sarmiento-Soto, Helia; López-Barneo, José; Muñoz-Cabello, Ana M. (Frontiers in Neuroscience, 2019)
Neurogenesis in developing and adult mammalian brain is a tightly regulated process that relies on neural stem cell activity. There is increasing evidence that mitochondrial metabolism affects neural stem cell homeostasis and differentiation but the precise role of mitochondrial function in the neurogenic process requires further investigation. Here, we have analyzed how mitochondrial complex I (MCI) dysfunction affects neural stem cell viability, proliferation and differentiation, as well as survival of the neural progeny. We have generated a conditional knockout model (hGFAP-NDUFS2 mice) in which expression of the NDUFS2 protein, essential for MCI function, is suppressed in cells expressing the Cre recombinase under the human glial fibrillary acidic protein promoter, active in mouse radial glial cells and in neural stem cells that reside in adult neurogenic niches. In this model we observed that survival of central neural stem cell population does not appear to be severely affected by MCI dysfunction. However, perinatal brain development was markedly inhibited and Ndufs2 knockout mice died before the tenth postnatal day. In addition, in vitro studies of subventricular zone neural stem cells showed that active neural progenitors require a functional MCI to produce ATP and to proliferate. In vitro differentiation of neural precursors into neurons and oligodendrocytes was also profoundly affected. These data indicate the need of a correct MCI function and oxidative phosphorylation for glia-like neural stem cell proliferation, differentiation and subsequent oligodendrocyte or neuronal maturation.